Molecular Characterisation of E. coli Isolated from Faecal Samples of Pups Affected with Canine Paroviral Enteritis - Warke, Shubhangi; Magar , Sunny (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Canine parvovirus (CPV) is one of the causative agents of enteritis and myocarditis in young puppies. In the present study 100 faecal  samples collected from dogs showing clinical sign of gastroenteritis were screened for detection of CPV antigen using Ubioquick VET  kit. Among these, 30 (30%) samples were found positive. These samples were further subjected to detailed bacteriological examination,  which revealed 22 (73.33%) samples positive for secondary bacterial infection, E. coli being predominant. Out of 22 dogs positive for  secondary bacterial infection, 14 (63.63%) dogs were infected with CPV + E. coli, 5 (22.72%) with CPV + Salmonella spp., and 3 (13.63 %)  with CPV + Klebsiella spp. The remaining 8 dogs had solo-infection with CPV. The predominant bacteria (E. coli) were further subjected  for detection of stx1, stx2 and eae gene by PCR. The stx2 gene amplicon of 584 bp was produced by all the 14 strains, while stx1 was not  detected in any of the isolates, and 3 (21.42 %) samples were found positive for eae gene with the amplicon of 877 bp. In vitro antibiogram  of the isolates associated with CPV infection revealed a maximum sensitivity towards ceftriaxone-tazobactam and ciprofloxacin (100%  each), followed by ceftriaxone and cefotaxime (55.55% each), amikacin (44.44%), furazolidone and amoxicillin-sulbactam (22.22% each),  and 100% resistace to metronidazole.
Keywords: AST; Canine parvovirus; E. coli; PCR; Secondary bacterial infection